Philosophy of Science and Philosophy of Science Review: Historical Analysis and Perspectives of Ontology, Epistemology, and Axiology - Asyha, Agus Faisal; Mustofa, Mustofa; Pahrudin, Agus; Munawar, Agus (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
Philosophy of science is a branch of philosophy that discusses the foundations, methodologies, and goals of science, as well as providing an ethical foundation for the development of science. This study explores the development of philosophy of science from the Ancient Greek period to the contemporary era, and analyzes the main dimensions of philosophy of science: ontology, epistemology, and axiology. Rational thinking in the Greek period, through figures such as Thales, Socrates, Plato, and Aristotle, became the basis of systematic science. In the golden age of Islam, figures such as Al-Farabi, Ibn Sina, and Al-Ghazali introduced an integration of revelation and reason that enriched